Economic evolution, identity dynamics and cultural science - Potts Jason (Cultural Science)
This paper introduces the concept of identity dynamics to evolutionary economic analysis. The extant literature on the economics of identity is reviewed and integrated into the micro- meso-macro model of evolutionary economic analysis. This model of identity dynamics serves to both generalise extant concern with the economics of identity as well as to integrate and develop broader psychological, social science and humanities models of identity in the context of open-system evolution as a contribution to cultural science.